THE ROLE OF THE NURSE IN MITIGATING THE EFFECTS OF FAKE NEWS ON VACCINE ADHERENCE: CHALLENGES AND STRATEGIES (CIPEEX, 2025)
The role of nursing in the face of the impacts of fake news on vaccine adherence has become increasingly relevant. The internet has intensified the dissemination of false news, generating significant concerns for the health sector. Therefore, understanding the challenges and developing effective strategies to achieve adequate vaccine coverage has become essential, with the nurse being a key figure in creating resources and meeting goals in this area. OBJECTIVE: To conduct a bibliographic research to analyze the role of the nurse in mitigating the impacts of fake news on vaccine adherence. METHOD: The study was conducted through a bibliographic review of articles published between 2018 and 2023. RESULTS: The difficulties associated with effective vaccine adherence were identified, and the necessary strategies for broad and effective coverage were described, highlighting the importance of the nurse in this context. CONCLUSION: The research comprehensively achieved its objectives, allowing for a detailed analysis of the ways in which the nurse can positively influence vaccine adherence. However, the topic is still recent and requires further depth, especially considering the continuous innovations in communication and technologies related to vaccines.
Keywords: Vaccine Adherence; Vaccine Coverage; Nurse; Fake News